A Scoping Review: The Role of Integrated Non-Communicable Disease (NCD) Programs In Improving Elderly Oral Health - Asterya Illa; Zahroh Shaluhiyah; Ayun Sriatmi (Fakultas Kedokteran Gigi, Universitas Mahasaraswati Denpasar, 2026)
Introduction: Oral health and non-communicable diseases (NCDs) in older adults are interconnected through shared behavioral, biological, and social risk factors. Dental caries and periodontal disease affect oral function and are associated with diabetes, cardiovascular disease, malnutrition, and reduced quality of life. However, oral health services and NCD management remain largely separated, limiting prevention and care coordination. This study aimed to map and synthesize evidence on the role of integrated NCD programs in improving oral health among older adults. A scoping review was conducted using the Arksey and O’Malley framework and PRISMA-ScR guidelines. Searches were performed in ProQuest, Scopus, and ScienceDirect for English-language articles published from 2021 to 2026. Eligible studies were descriptively analyzed and narratively synthesized. Review: Thirteen original studies met the inclusion criteria: ten cross-sectional, two qualitative, and one descriptive study. Findings demonstrated associations between oral health and NCD-related conditions, particularly cardiovascular risk, malnutrition, and periodontal disease severity. Interprofessional collaboration, community-based screening, and social support were identified as key components of integrated care. Community education and home-visit models improved service utilization, although healthcare access barriers and primary care infrastructure gaps persisted. Conclusion: Integrated NCD programs may improve oral health among older adults through holistic and collaborative care, but policy support and sustainable implementation strategies are essential.